First iodocyclization reaction of allene-thioureas: an efficient approach to bicyclic beta-lactams - Garud, Dinesh R.; Jadhav, Amol R.; Lahore, Santosh V.; Kahar, Nilesh M.; Joshi, Rohini R.; Joshi, Ramesh A.; Koketsu, Mamoru (Tetrahedron Letters, 2014)
The regioselective iodocyclization reaction of allene-thioureas is described, for the first time, for the synthesis of bicyclic beta-lactams. The substitution at the allenyl part heavily influenced the iodocyclization reaction. The iodocyclization reaction of the unsubstituted allene-thioureas afforded six-membered 3-thia-1-dethiacephems whereas, the substituted allene-thiourea afforded seven-membered thiazepines along with five-membered isopenams. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Allene; beta-Lactams; Iodocyclization; Regioselective; thiourea

Biomass derived beta-cyclodextrin-SO3H as a solid acid catalyst for esterification of carboxylic acids with alcohols - Thombal, Raju S.; Jadhav, Amol R.; Jadhav, Vrushali H. (RSC Advances, 2015)
A novel beta-cyclodextrin-SO3H carbon based solid acid catalyst was prepared in a convenient and ecofriendly manner and was characterized using FTIR, PXRD, EDAX and NH3TPD to illustrate that the carbon material has been functionalized with -SO3H, -COOH and -OH groups. The catalyst was studied for esterification of various carboxylic acids and alcohols under solvent free conditions and showed excellent catalytic performance and gave good yields of esters in the range 78-99% at 70 degrees C. No solvent was used either for catalyst preparation nor for esterification reaction. The catalyst can be easily recovered by simple filtration and reused for subsequent three runs without any significant impact on yields of products. The main advantage of this methodology is easy and ecofriendly catalyst preparation, easy catalyst separation, practical simplicity, safe reaction conditions, recyclable catalyst and high product yields.

Synthesis of (+/-) debenzoyl analogs of norsampsones as potential anticancer agents - Jadhav, Amol R.; Thombal, Raju S.; Nigam, Preeti; Jadhav, Vrushali H. (Tetrahedron Letters, 2015)
Synthesis of (+/-) debenzoyl analogs of norsampsones 1 and 2 is reported starting from commercially available 1,3-cyclohexadione in six steps with overall yields of 37% and 36%, respectively. Compounds 1 and 2 were tested for their anticancer activity and showed moderate anticancer activity against HeLa cell lines. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Acylphloroglucinols; Anticancer; Debenzoyl; Norsampsones

Efficient method for the synthesis of quinoxaline derivatives catalyzed by titanium silicate-1 - Chandrachood, Pranav S.; Jadhav, Amol R.; Garud, Dinesh R.; Deshpande, Nirmala R.; Puranik, Vedavati G.; Kashalkar, Rajashree V. (Research on Chemical Intermediates, 2020)
A series of quinoxaline derivatives were efficiently synthesized by convenient and simple procedure in excellent yields using 1 wt.% of titanium silicate (TS-1) catalyzed reaction of 1,2-diamines and 1,2-diketones in methanol at room temperature. This reaction is scalable to multigram scale and the catalyst is recyclable. [GRAPHICS] .
Keywords: 2-Diketones; Aromatic 1; o-Phenylenediamine; Quinoxaline; Room temperature; Titanium silicate-1